PENGARUH DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA KANTOR LURAH ARGAPURA KOTA JAYAPURA - Munawir Lobubun (ark:/00000/jeb.v12i1, 2021)
The results of the calculation using the SPSS Version 22 application are that work discipline has a positive and significant effect on the performance of the state civil apparatus at the Argapura Village Head Office, Jayapura City, so that the hypothesis that work discipline affects the performance of the state civil apparatus is acceptable, meaning that work discipline has a positive and positive effect. significant impact on the performance of the state civil apparatus at the Argapura Lurah Office, Jayapura City. The value of the correlation coefficient (R) indicates that the work discipline variable (X) has a strong relationship with the performance variable of the state civil apparatus (Y) at the Argapura Lurah Office, Jayapura City. In addition, the value of the coefficient of determination R2 indicates that there is an influence of work discipline on the performance of the state civil apparatus at the Argapura Lurah Office, Jayapura City, by 82.5%, while the rest is influenced by other variables or factors not examined.